Kajian Bentuk dan Makna Simbolik Figurin Gerabah Majapahit (Periode Hayam Wuruk 1350-1389 M) - Anne Susannawaty (Journal of Visual Art and Design, 2008)
The earthware figurines of Majapahit  were clay-based artworks from the Majapahit Kingdom (1350-1389 AD) of Trowulan at Mojokerto, East Java. The name "majapahit" itself refers to the known great kingdom that unite "nusantara" (covering Malay peninsula, Sumatra, Java, Bali, Borneo, Celebes, up North to the Southern of Phillipine). Having exposed to the varieties and high-quality of earthware figurines of Majapahit from the Trowulan site, the study looks into their symbolic shapes and meanings which was known to be heavily influenced by Hinduism. To address this issue, the study applied qualitative-descriptive method by means of visual analysis. Study on clay-objects' shapes was carried out to explore the associated meanings of 4 (four) figurine groups: (1) male figurines, (2) female figurines, (3) child figurines, and (4) deformed-face figurines. Results indicate that shapes of the object cater their symbols and associated meanings to the way religion and/or beliefs were held. Figure of gods, kings, and the nobles were made to manifest values (truth, heroism, devotion,and loyalty). Yet, although Hinduism was the most associated values to appear on the objects, Budhism were also identified.This shows that earthware figurines of Majapahit were product of acculturation where different values are met, explored, and exposed to appease the spirits (dharma) through ritual and performance.